Development of Islamic boarding school-based learning tools on social arithmetic material to improve students' numeracy skills - Habibi, Ahmad Anas; Lestari, Nurcholif Diah Sri; Kurniati, Dian; Susanto; Yudianto, Erfan; Sanawi, Ihsan (UNNES JOURNAL, 2024)
The numeracy abilities of students in Indonesia are still considered inadequate or quite low and must continue to be improved. One of the efforts made to improve students' numeracy abilities is by implementing learning tools that can support the development of these abilities. The research aims to develop learning tools that can be declared valid, practical, and effective, especially in social arithmetic material, and improve students' numeracy skills. This research is development research with the 4D model from Thiagarajan. Thiagarajan's 4D stages include the definition, design, development, and deployment stages. The data collection techniques used are observation, questionnaires, and tests. The research results on developing Islamic boarding school-based learning tools are classified as valid, practical, and effective. The level of validity can be seen from the validation value: for the teaching module, it is 3.47; LKPD is 3.44; for the learning achievement test, it is 3.32; and the manual is 3.31 (maximum score 4), which is included in the valid category. The practicality value obtained from the students' activities was 90.7%, which was in the very good category; the implementation of learning was 3.56, which means high value; as well as the students' response questionnaire showed a positive value. The effectiveness value seen from the students' learning outcomes data was obtained at 87.0% classical completion. Not only that, but effectiveness can also be seen from the students' numeracy ability test, namely the results pre-test, which was an average of 34.87% increase in revenue post-test to 82.0%, which was then analyzed using the N-Gain test to obtain an average result of 0.73 which was included in the high category. Thus, Islamic boarding school-based learning tools on social arithmetic material can effectively be used to improve students' numeracy skills. Kemampuan numerasi peserta didik di Indonesia masih tergolong kurang atau cukup rendah dan masih harus terus ditingkatkan. Salah satu upaya yang dilakukan untuk meningkatkan kemampuan numerasi peserta didik adalah dengan menerapkan perangkat pembelajaran yang dapat menunjang berkembangnya kemampuan tersebut. Adapun penelitian yang dilakukan ini memiliki tujuan untuk mengembangkan perangkat pembelajaran yang dapat dinyatakan valid, praktis, dan efektif, khususnya pada materi aritmatika sosial serta mampu meningkatkan kemampuan numerasi santri. Penelitian ini termasuk dalam jenis penelitian pengembangan dengan model 4D dari Thiagarajan. Tahapan 4D dari Thiagarajan mencakup tahap pendefinisian, perancangan, pengembangan, dan penyebaran. Teknik pengumpulan data yang digunakan adalah observasi, angket, dan tes. Hasil dari penelitian pengembangan perangkat pembelajaran berbasis pesantren tergolong ke dalam kriteria valid, praktis, dan efektif. Tingkat kevalidan dapat dilihat dari nilai validasi, untuk modul ajar sebesar 3,47; LKPD sebesar 3,44; tes hasil belajar sebesar 3,32; dan buku petunjuk sebesar 3,31 (skor maksimal 4) yang termasuk pada kategori valid. Nilai kepraktisan diperoleh dari aktivitas santri sebesar 90,7% yang masuk dalam kategori sangat baik, keterlaksanaan pembelajaran sebesar 3,56 yang berarti bernilai tinggi, serta angket respon santri yang menunjukkan nilai positif. Nilai keefektifan dilihat dari data hasil belajar santri diperoleh 87,0% tuntas secara klasikal. Tidak hanya itu, keefektifan dilihat dari tes kemampuan numerasi santri, yakni hasil pre-test yang semula rata-rata 34,87% meningkat pada hasil post-test menjadi 82,0%, yang kemudian dianalisis menggunakan uji N-Gain dengan memperoleh hasil rerata 0,73 yang masuk dalam kategori tinggi. Dengan demikian dapat disimpulkan bahwa perangkat pembelajaran berbasis pesantren pada materi aritmatika sosial sudah layak untuk digunakan dan terbukti efektif untuk meningkatkan kemampuan numerasi santri.